2021
DOI: 10.1093/rheumatology/keaa789
|View full text |Cite
|
Sign up to set email alerts
|

Arterial wall inflammation is increased in rheumatoid arthritis compared with osteoarthritis, as a marker of early atherosclerosis

Abstract: Objective RA is associated with higher risk of cardiovascular (CV) disease. Ongoing systemic inflammation is presumed to accelerate atherosclerosis by increasing inflammation in the arterial wall. However, evidence supporting this hypothesis is limited. We aimed to investigate arterial wall inflammation in RA vs OA, and its association with markers of inflammation and CV risk factors. Methods 18-fluorodeoxyglucose PET combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“… 31–35 In atherosclerosis, the evaluation of TBR was suitable to detect vessel wall inflammation 20 24 and the composition of plaques. 20 21 23 In RA, Agca et al 24 found increased arterial wall inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 31–35 In atherosclerosis, the evaluation of TBR was suitable to detect vessel wall inflammation 20 24 and the composition of plaques. 20 21 23 In RA, Agca et al 24 found increased arterial wall inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…14 There have been reports on the examination of joints or blood vessel inflammation in RA by positron emission tomography (PET) or PET/CT. [17][18][19][20][21][22][23][24][25][26] There is increased 18 F-fluorodeoxyglucose (FDG) uptake in the arterial wall in RA, 24 26 27 as well as ankylosing spondylitis (AS) 28 and psoriatic arthritis. 29 18 F-FDG-PET was able to follow disease activity, joint destruction and…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 18F-FDG PET/CT imaging is usually applied to detect the glucose uptake and metabolic changes in human diseases 37 using 18F-fluorodeoxyglucose (18F-FDG), a radioactively labelled glucose analogue, which is injected into the body to reflect the status of metabolism activities through the aggregation of radioactivity. 38,39 The 18F-FDG uptake was associated with serological and clinical markers of inflammation, 40 and the role of 18F-FDG PET in imaging inflammatory conditions has been validated in KOA. 41 The high expression of GLUT-1 receptor subtype in stimulated inflammatory cells such as macrophages is one of the potential mechanisms for 18F-FDG uptake in these inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Clinical trials investigating arterial inflammation using FDG-PET imaging showed increased FDG aortic uptake in RA patients. 76 , 77 The central role of the inflammation is also supported by the mitigative effects of anti-inflammatory treatment regimens on the CVD risk. 7 , 46 , 49 , 78 , 79 The double-impact of inflammation on both RA progression and increased CVD risk led some authors to suggest that treatment with biologic DMARDs (such as TNF alpha inhibitors) amounts to “killing 2 birds with 1 biological stone.” 80 Currently ongoing TARGET trial ( https://targetra.org ) is aimed at understanding how different treatments for RA affect cardiac inflammation.…”
Section: Discussionmentioning
confidence: 99%